Independent associations between loneliness, self-reported hearing loss, and episodic memory: findings from the Northern Ireland Cohort for the Longitudinal Study of Ageing (NICOLA). - Loughrey, David G.; Feeney, Joanne; Kee, Frank; Lawlor, Brian A.; McGuinness, Bernadette; Woodside, Jayne V.; Neville, Charlotte E.; Power, Joanna McHugh (Aging & Mental Health, 2026)
Objectives: Age-related hearing loss (ARHL) and loneliness have been independently associated with poor cognitive function in older adults. However, the extent to which loneliness modifies the relationship between ARHL and cognitive impairment remains poorly understood. This study examined the independent and interactive associations of ARHL and loneliness with episodic memory in older adults. Method: We used cross-sectional data from wave 1 of the 2,471 community-dwelling adults aged over 50 years from the Northern Ireland Cohort for the Longitudinal Study of Ageing (NICOLA) study. ARHL was assessed via a latent 'hearing quality' factor derived from self-rated items. Loneliness was measured using a modified UCLA Loneliness Scale, and episodic memory through immediate and delayed word recall tasks. Data analysis was performed using regression models. Results: Higher loneliness and poorer self-reported hearing loss were independently associated with worse immediate recall. Only loneliness was associated with delayed recall. No significant interaction between ARHL and loneliness was observed for any memory outcome. Conclusion: Findings suggest that ARHL and loneliness contribute separately to poorer episodic memory in later life. Loneliness and ARHL do not appear to interact in their associations with episodic memory. Further longitudinal and biomarker-informed research is needed to clarify causal pathways linking ARHL with cognitive function in later life.